2163. RSV-related hospitalization and outpatient palivizumab use in very preterm (born at < 29 wGA) infants: 2003-2020. (15th December 2022) - Packnett, Elizabeth; Larkin, Heather; Winer, Isabelle; Diakun, David R; Oladapo, Abiola; Gonzales, Tara L; Wojdyla, Matthew
Abstract: Background: Respiratory syncytial virus (RSV) is the leading cause of bronchiolitis and pneumonia in children under one year and the leading cause of infant hospitalization. Palivizumab was approved by the FDA in 1998 as RSV immunoprophylaxis (RSV-IP) to prevent severe RSV disease in children with specific health conditions and those born at < 35 weeks gestational age (wGA). Though RSV-IP recommendations have changed over time, RSV-IP has been consistently recommended in very preterm infants (< 29 wGA) since palivizumab approval. This study's objective is to compare RSV-related hospitalization (RSVH) and RSVH characteristics in very preterm and term ( > 37 wGA) infants. Methods: Using the MarketScan Commercial and Multi-State Medicaid administrative claims databases, very preterm and term infants born between 7/1/2003 and 6/30/2020 were identified and classified as very preterm or term using diagnosis codes. Infants with evidence of health conditions such as congenital heart disease and cystic fibrosis were excluded. During 2003-2020 RSV seasons (November to March), claims incurred by infants while they were < 12 months old were evaluated for outpatient administration of palivizumab and RSVH. RSVH was identified in infants with an inpatient claim with an RSV diagnosis. Rate of RSVH during the first 12 months of life was calculated and compared in very preterm and term infants; the proportion of very preterm infants with an outpatient administration of palivizumab was also calculated. Results: The study included 40, 123 very preterm infants and 4, 421, 942 term infants. Rate of RSVH in very preterm infants ranged 1.5-3.8 per 100 infant seasons in Commercially insured infants and 3.5-8.4 in Medicaid insured infants. Relative risk of RSVH in very preterm was 3-4 times higher than term infants and was inversely related to wGA at birth (Figure 1). ICU admissions and mechanical ventilation were more common during RSVH in very preterm infants (Table 1); these outcomes were less common in very preterm infants with outpatient palivizumab administration (Table 2). Figure 1. Relative risk of RSVH in very preterm vs. term infants Table 1. RSVH characteristics of term and very preterm infants by payer Table 2. RSVH characteristics of very preterm infants by palivizumab use and payer Conclusion: Rates of RSVH are significantly higher and RSVH is more severe in very preterm infants than in term infants. Among very preterm infants, RSVH was less severe in infants with outpatient palivizumab administration. Disclosures: Elizabeth Packnett, MPH, IBM Watson Health: Employee|Sobi: Contracted IBM Watson Health to conduct the study. Isabelle Winer, MPH, IBM Watson Health: employee|Sobi: contracted IBM Watson Health to conduct study David R. Diakun, BS, Sanofi: Employed by IBM Watson Health which was contracted by Sanofi to perfom outcomes research|Sobi: Employed by IBM Watson Health which was contracted by Sobi to conduct the study Abiola Oladapo, PhD, Sobi Inc: Employee Tara L. Gonzales, MD, Sobi, NA: Employee Matthew Wojdyla, PharmD, Sobi: Employee.